A new multilayered membrane for tissue engineering of oral hard- and soft tissue by means of melt electrospinning writing and film casting – An in vitro study. Issue 4 (April 2019) - Fuchs, Andreas; Youssef, Almoatazbellah; Seher, Axel; Hartmann, Stefan; Brands, Roman C.; Müller-Richter, Urs D.A.; Kübler, Alexander C.; Linz, Christian
Abstract: Membranes that form a mechanical barrier not only for cells but also for the bacterial flora of the oral cavity may be helpful in infection-free wound healing for guided tissue regeneration (GTR) applications in the field of oral- and maxillofacial surgery. Controlled wound healing without interference from bacterial contamination appears to be achievable in combination with surface scaffolds for bone- and soft tissue regeneration. As this has not yet been realized, we developed multilayered membranes in this study consisting of specific surface scaffolds for bone- and mucosal regeneration as well as bacteria-tight core membranes. These membranes were evaluated in terms of cell growth of osteoblast- (MG63), keratinocyte- (HaCaT), and fibroblast (L929) cell lines. Scaffolds were fabricated via melt electrospinning writing (MEW), while the core membrane was produced via film casting. All constructs were made of medical-grade poly(ε-caprolactone) (PCL). The bacteria-tightness was tested via a bacterial transmigration-assay. PCL scaffolds and core membranes alone demonstrated good cytocompatibility for all cell lines, which was even enhanced by fusing both components together. The core membrane displayed complete bacteria-tightness over two weeks. These bacteria-tight, individually-designed membranes from medical-grade PCL represent a high-potential, clinically oriented method of GTR in the field of oral- and maxillofacial surgery.